(untitled) (Revista Contexto & Saúde, 2025)
Objective: Investigate from the clinical epidemiological profile, factors that may influence the possibility of Postpartum Depression (PPD) in pregnant women assisted at the Santa Casa de Misericordia do Pará Foundation. Methods: This was a prospective, descriptive, cross-sectional cohort study with a quantitative approach. Two questionnaires were applied: one for self-assessment of postpartum depression, based on the Edinburgh Postpartum Depression Scale, and another, developed by the researchers themselves, containing information on sociodemographic data and maternal obstetric history. The questionnaires were applied to postpartum women. The established cut-off point was greater than or equal to 10, with a sensitivity of 82.6% and a specificity of 65.4%. Statistical significance was analyzed by the G and Chi-Square Adherence Tests, adopting a significance level of 5%. Results: 214 questionnaires were collected. The prevalence of Ages was 20-29 years old, completed high school, unemployed, breastfeeding and nulliparous. Of the complications during pregnancy hypertensive disorders showed statistical significance. In the group studied, there was no relationship between the types of parturition with the PPD. The existence of a correlation between PPD and breastfeeding, the newborn’s weight and the mother’s mood was verified. Conclusion: No association was found between the type of parturition and the presence of postpartum depression. Of the factors that showed significance, there are breastfeeding and birth weight, which are important markers of maternal and child health care, and it is necessary to emphasize the primordiality of stimulating breastfeeding soon after birth while still in the maternity ward also relating to the mother-baby bond as a protective factor.